Čh̨̄omphon P̨̄o. Phibūnsongkhrām kap Čhangwat Lop Burī (Chomrom ʻAnurak Bōrānnawatthusathān læ Singw̄ætl̨̄om Čhangwat Lop Burī, 1993)
Contributed articles on urban development plans at Lop Buri Province, Thailand during Pl̄æk Phibūnsongkhrām, 1897-1964, prime minister tenure.